PENGEMBANGAN GAMEEDUKASI TAJWID MENGGUNAKAN ADOBE FLASH CS6 PADA MATERI AHKAMUL HURUF KELAS IV SEKOLAH DASAR - Umairah, Saidati Jannati; Trisoni, Ridwal; Haviz, M. (State Institute for Islamic Studies Batusangkar, 2019)
The main problem of this research is the learning of Al-Quran education in Elementary Schools which only uses conventional media, and the lack of varied use of media. This results in a lack of interest and interaction of students in following the learning process. The purpose of this research is to produce a valid and practical learning media. This research uses a development research method that is a process or steps to develop a new product or improve existing products, which can be accounted for. The research development design and procedures used are 4-D models, namely define, design, develop and disseminate. This research did not carry out the disseminate stage. The research instrument used questionnaire validation sheets and response questionnaires. Based on the results of research that has been done, categorized games are very valid with a percentage value of 93.75% and practical with an index value of 92%. It can be concluded that this game can be used as a learning medium for Al-Quran Education and help students understand the material of the letters ahkamul.